Spatial and temporal distribution of p21 senescent cells in periodontal tissue of diabetic mice - YI Zimei; REN Le; WEI Yu; CHEN Siyi; YAN Jiayu; WU Junhua (Kouqiang hemian waike zazhi)
[Objective:] To investigate the spatial and temporal distribution of p21 senescent cells in periodontal tissue and femur of diabetic mice. [Methods:] We constructed transgenic mice capable of tracing p21 senescent cells, used gel electrophoresis assay to screen 24 homozygous mice, and randomly divided them into control group and diabetic group, with 12 mice in each one. The control group was given a normal diet, while the diabetic group was given a high fat diet for 4 weeks, followed by streptozocin (STZ) injection to induce the diabetic model. Periodontal tissue samples were collected from mice at 4, 8, 12, and 16 weeks respectively. We used the tracer function of p21-3MR mice and real-time quantitative polymerase chain reaction (RT-qPCR) to investigate the spatial and temporal expression changes of p21 senescent cells and periodontal changes in inflammation levels. [Results:] The expression levels of p21 increase over time during the progression of diabetes, and the distribution of p21 senescent cells gradually extends from the gingiva towards the alveolar bone. [Conclusion:] p21 senescent cells are involved in the progression of diabetes and may play a role in the regulation of bone homeostasiss by secretion of senescence-associated secretory phenotype (SASP) factors, but their specific mechanisms require further investigation.